Financial instruments disclosure practices : evidences from Malaysian listed companies - Syaima' binti Adznan (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2014)
The current changes in business settings have directed companies to conduct business at international level, which requires the use of financial instruments. The mandatory MFRS 7, an-equivalent to the IFRS 7 standard shall be applied for annual financial periods beginning or after 1 Jan 2012. It caters for entities to disclose their involvement with financial instruments. Thus, the aim of this study is to investigate the financial instruments disclosure (FID) practices of Malaysian listed companies; specifically, their level of compliance with MFRS 7. The mean score for FID is 80.76%, which indicates that, in general, companies have complied with MFRS 7, although there are several requirements omitted by some companies. Furthermore, in light of the revision of MCCG in 2012, this study examines the association of corporate governance mechanisms with the extent of FID among companies. The corporate governance characteristics used in this study are board expertise, audit committee independence, audit fee, external and internal audit functions. This study applied the agency theory and formulated five hypotheses to test the extent of the relationship between FID and corporate governance characteristics. Based on a total sample of 319 Malaysian public listed companies for financial year end 2012, the analysis revealed that FID is significantly and positively associated with audit committee independence and external audit functions, while internal audit is negatively associated. The results suggest that audit committee members need to be independent to discharge their duties effectively; in addition, there should be an internal audit function that is independent, reliable and functioning in a timely manner. This is crucial in order to strengthen the role of the auditing function within the firm. Moreover, the results attest that, Big Four audit firms are more likely to ensure high compliance with applicable accounting standards compared to non-Big Four, as they are internationally recognised, and have more resources and expertise. Apart from contributing to the literature on financial reporting and corporate governance, this study may serve as a valuable input for regulators and standard setters to encourage strict enforcement of the incorporation of effective corporate governance practices in Malaysian listed companies, as this is likely to have some influence on the level of compliance with MFRS.